Influence of soil type, cultivars, previous crop and growth stage on population of Meloidogyne spp. and Rhizoctonia spp. on tomato - Sagar, B Vidya; Rao, V Krishna; Varaprasad, K S (Indian Journal of Plant Protection, 2020)
The density and frequency of occurrence of Meloidogyne and Rhizoctonia, associated with tomato in Andhra Pradesh, were found to be influenced by various ecological factors, viz. soil type, cultivars, previous crop grown and stage of crop growth. The population of Meloidogyne was maximum in the loamy soil, cultivar Tulasi when the previous crop was water melon and at the flowering stage. Minimum population was observed in clay loam soils, cultivar Sridevi, when previous crops were onion, maize, paddy or when field kept fallow and at vegetative stage. Similarly, the maximum population of Rhizoctonia was observed in sandy loam soil, in US618 cultivar, when previous crop was potato and at flowering stage.